Benefits and tensions in delivering public health in community pharmacies – a qualitative study of healthy living pharmacy staff champions. (29th November 2016) - Cooper, Richard J.; Tsoneva, Jo
Abstract: Objective: Healthy Living Pharmacies (HLP) were introduced in the United Kingdom (UK) in a further attempt to deliver public health benefits in community pharmacy settings. Central to the initiative are staff trained as Healthy Living Champions (HLC) and this study sought to explore HLC perceptions of positive and negative aspect of their work and the wider scheme. Methods: A qualitative study was undertaken with a purposive sample of HLCs working in pathfinder HCPs in the Sheffield area in 2014. Participants were recruited by email to either a focus group ( n = 7) held at a training event or later semi‐structured one‐to‐one interviews in pharmacies ( n = 6). Four stages of interpretative phenomenological analysis were used to code and identify themes. Key findings: Four main themes emerged relating to the positive workforce development impact HLPs had upon HLCs themselves and on perceived customer and patient engagement and benefits. Tensions were identified with existing commercial business demands and negative views overall of the pharmacy setting with a perceived lack of not only integration with other services but also awareness among the public and health care staff. HLCs felt empowered and more confident in initiating conversation about health issues with patients, but identified barriers relating to workload, a lack of time to perform their role, isolation, tensions with non‐HLC staff and logistical barriers such as poor Internet access. Conclusions: Delivering public health activities through the HLC role in UK pharmacies is associated with several perceived benefits for different stakeholders, but may be threatened by well recognised barriers in UK pharmacies related to the commercial setting.